PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN MELALUI MICROSOFT POWERPOINT BAGI GURU SDN 4 RARANG KABUPATEN LOMBOK TIMUR - Nukman, Nukman; Khulaimi, Muhammad; Rachman, Dedy Febry (INSANTA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The goal that will be achieved through this community service is that teachers have the knowledge and skills to produce learning media in the form of learning videos made via Microsoft Power Point. Power Point is a simple choice because it is easy for teachers to operate and master. The methods used in training to make learning videos are lectures, discussions, questions and answers, and practice. The number of participants who attended the training was eleven participants. The training material consists of two, namely first, delivered by Muhammad Hulaimi S.Kom. M.T. regarding the purpose and benefits of learning videos. Second, delivered by Nu'man, S.Kom. M.T. regarding how to make learning videos using Microsoft Power Point technically and practically. The training in making learning videos was highly appreciated by the school. This is very useful for teachers in the learning process and developing teacher professionalism in the current era. As a result of this training, several teachers succeeded in making learning videos.